The Impact of Open-Market Share Buyback Announcements by Leading European Companies - Ács, Márton; Malatinszky, Gabor (Public Finance Quarterly, 2025)
We analyzed a sample of open market repurchase announcements from 76 leading European companies included in the Stoxx Europe 600 index between 2020 and 2024 and found a significant average cumulative abnormal return of 1.11% within a 3-day event window. Our findings revealed that market reactions were significant during the period between 2020 and 2022, amidst uncertainties caused by the spread of the COVID-19 pandemic and the outbreak of the Russian-Ukrainian war, whereas no significant reactions were observed in the calmer market environment of 2023 and 2024. At the company level, differences in market effects were explained by capital structure theory, indicating that the market particularly rewarded the open market repurchases of firms with leverage ratios below target, prior to the announcements. Importantly, during crises, this effect was only present if leverage levels remained moderate even after the equity transactions.